Effect of BTS (Behind-the-Scenes) content marketing via Tiktok on the perceptions and behavior of consumers toward artisanal businesses - Artesano, Janille Marie A.
Along with the rise of TikTok is the mergence of artisanal businesses that thrived around the COVID-19 pandemic timeline.Given that brands started to incorporate their products through trends, knowing their audiences, and maximizing the platform's potential, this study aims to determine how BTS (Behind-the-Scenes) Content Marketing via TikTok affects the Perceptions and Behavior of Consumers Towards Artisanal Bussinesses. The first part of the study profiled the respondents according to sex, socioeconomic status, and hours spent on TkTok. This study determined the consumers' perception toward artisanal businesses according to the consumer-brand relationship: scenariomexposure,perceived amount of brand information disclosure (manipulation check), and consumer brand relationship quality. Also, this study described the behavior of the consumers toward artisanal businesses according to liking, intimacy and trust, and overall brand perception. And lastly, this study measured the relationship in the perception and behavior of the consumers towards artisanal business. The researchers used experimental and comparative research designs since there was an intervention and manipulation of the researchers on the independent variable.The researchers conducted the survey online and targeted 18 to 24 years old TikTok users and used the snowball sampling method. The study showed no significant difference in consumer behavior towards artisanal businesses that use behind-the-scenes content marketing when grouped according to their demographics, accepting the hypothesis. Findings of this study reveal that the aspect of trust is very high, followed by intimacy, supporting Taylor's (1973) Social Penetration Theory. However, results show a positive correlation and significant relationship between consumer perception and behavior toward artisanal businesses using behind-the-scenes content, specifically Behind-the Scenes content marketing disclosing information about employees or people behind the brand.